2011
DOI: 10.1089/acm.2010.0215
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Psychosocial Effects of Health Qigong in Patients with COPD: A Randomized Controlled Trial

Abstract: This RCT provided some evidence to support the positive effect of HQG as an adjunct home exercise for rehabilitation among people with COPD and to support further related research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(129 citation statements)
references
References 34 publications
3
124
1
1
Order By: Relevance
“…All the included trials except one 12 described the details involving the duration, frequencies, and session length of the interventions. Seven trials measured the outcomes for 3 months, [9][10][11][12][13][14][15] while the other three trials measured outcomes for 6 months 16,17 11,18 to two sessions per day and 7 days per week. 15 One trial made the patients self-practice t'ai chi and qigong daily after the supervised sessions.…”
Section: Trials Characteristicsmentioning
confidence: 99%
“…All the included trials except one 12 described the details involving the duration, frequencies, and session length of the interventions. Seven trials measured the outcomes for 3 months, [9][10][11][12][13][14][15] while the other three trials measured outcomes for 6 months 16,17 11,18 to two sessions per day and 7 days per week. 15 One trial made the patients self-practice t'ai chi and qigong daily after the supervised sessions.…”
Section: Trials Characteristicsmentioning
confidence: 99%
“…Intention-to-treat analysis for missing data was not employed in three studies [35,37,38]. One study [51] reported more than 15% attrition rate, along with the unclear description of point measure and measures of variability.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Only two studies [51,52] used isolated Baduanjin training to compare with other control conditions. Intervention duration in Baduanjin training varied greatly across studies selected, ranging from 3 to 12 months.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…At the end of the trial, there were no significant differences between the two groups. [44] Cineole (Eucalyptus, Myrtaceae) has positive effects on the beat frequency of the cilia and bronchodilation, it may show positive influence on the exacerbations of COPD and lung function tests. Patients who received 200 mg of cineole tablets three times a day had a reduction of exacerbations such as dyspnea and improvements of lung function and health status.…”
Section: Plant-based Therapies For Copdmentioning
confidence: 99%
“…Patients who received 200 mg of cineole tablets three times a day had a reduction of exacerbations such as dyspnea and improvements of lung function and health status. [44] • Astragalus (Milk Vetch Root, Huang Qi, Leguminosae) and Codonopsis pilosula are used for their immune modulatory and anti-inflammatory effects. The effects of Astragalus polysaccharides (APS) and C. pilosula polysaccharides on alveolar macrophage (AM) phagocytosis and inflammation in COPD.…”
Section: Plant-based Therapies For Copdmentioning
confidence: 99%